1990
DOI: 10.1007/bf00053431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketanserin of left ventricular hypertrophy in hypertensive patients

Abstract: Ketanserin, a serotonergic S2-receptor antagonist, was used in a prospective study in nine hypertensive patients with ECG criteria of left ventricular hypertrophy (LVH). Echocardiographic measurement with M mode was made after 1 month of placebo, and after 3, 6, and 12 months of ketanserin treatment as monotherapy at a mean dose of 31 mg bid. Ketanserin treatment decreased mean left ventricular mass by 9.3% at 3 months (not significant), by 15.3% at 6 months (p less than 0.008), and by 26.2% at 12 months (p le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Ketanserin, through blockade of serotonin-induced platelet aggregation and vasoconstriction, both of which increase with age, is targeted for elderly hypertensive patients [26]. Ketanserin was recently reported to achieve regression of LV hypertrophy in older hypertensive patients without concomitant deleterious effects on LV function [27,28]. These findings in nine and 13 patients followed for 12 months corroborate earlier data and are similar to those of the present study [10,29].…”
Section: Discussionsupporting
confidence: 82%
“…Ketanserin, through blockade of serotonin-induced platelet aggregation and vasoconstriction, both of which increase with age, is targeted for elderly hypertensive patients [26]. Ketanserin was recently reported to achieve regression of LV hypertrophy in older hypertensive patients without concomitant deleterious effects on LV function [27,28]. These findings in nine and 13 patients followed for 12 months corroborate earlier data and are similar to those of the present study [10,29].…”
Section: Discussionsupporting
confidence: 82%
“…In this regard, it is interesting to note that ketanserin has been shown to reduce left ventricular hypertrophy while preserving cardiac function in hypertensive patients (26), and the 5-HT antagonist sarpogrelate attenuates the ability of the hypertrophic agonists angiotensin II and endothelin-1 to stimulate protein synthesis in cardiomyocytes (27).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed that 5-HT 2A receptors mediated positive inotropic response in ventricular myocytes and were overexpressed in different models of cardiac hypertrophy, along with human heart failure 7, 28. Additionally, 5-HT 2A receptor blockade reverses hypertrophy during pressure overload and reduces left ventricular hypertrophy 8, 29. 5-HT 2B receptors have also been implicated in ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 96%